Literasi Kesehatan Mental Majelis Taklim Melalui Psikoedukasi Islami - Efrita Norman; Yanti Hasbian Setiawati Norman; Yunia Kusminarsih; Ria Amriah Malili (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aimed to improve the mental health literacy of Majelis Taklim members through an Islamic psychoeducation approach as an effort to strengthen community character in a rural area of Bogor Regency. The activity was conducted using a community-based participatory approach, including coordination with community partners, pre-test, interactive lectures, focused group discussions, religious coping practices (self-reflection and dhikr), and post-test evaluation followed by joint reflection. A total of 30 Majelis Taklim members participated in the program. The evaluation results using a 5-point Likert scale indicated improvements across all mental health literacy indicators, including basic mental health knowledge, attitudes toward stigma, help-seeking intentions, and the use of adaptive coping strategies. These findings suggest that Majelis Taklim serves as an effective community-based platform for mental health promotion that is culturally and religiously appropriate. In addition, the program contributed to strengthening prosocial character values such as empathy, patience, gratitude, and social responsibility. This community service activity is recommended to be implemented sustainably through collaboration between Majelis Taklim, village government, and educational institutions.